Pengolahan Dan Kualitas Limbah Cair Hotel Swiss-Bell Panakukkang Di Kota Makassar Tahun 2017 - Abd Gafur; Aninditta Putri Fitriyanti; Rahman Rahman (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX, 2019)
The existing problem at Hotel Swiss-Bel Panakukkang is that the hotel does not have Liquid Waste Disposal Permit (IPLC), has not recorded daily wastewater pH, has not recorded daily wastewater discharge, has not checked periodic wastewater quality parameter standard 1 ) Within 1 (one) month, has not submitted daily waste water discharge report, daily pH and wastewater parameters at least once in 3 (three) months to BLHD Makassar with copies of BLHD South Sulawesi Province. This study aims to determine the processing and quality of liquid waste Swiss Hotel-Bell Panakukkang Makassar Year 2017 viewed from the parameters of pH, BOD, COD, TSS and ammonia. The type of this research is observasional with descriptive approach. The results showed that there are still parameters that exceed the quality standard because it is not in accordance with the Minister of Environment Regulation No. 5 of 2014 on the Standard of Liquid Waste for Hospitality Activities. On average inlet pH 6.8 and average outlet pH level of 6.15. In the mean inlet BOD content of 79.82 mg / L and outlets of 138.78 mg / L. On average inlet COD 120 mg / L and outlet 200 mg / L. In the average inlet TSS content of 45.5 mg / L and outlet of 88 mg / L. In the average inlet and outlet for ammonia <0.01 mg / L. Wastewater treatment is done with five times phase: preliminary treatment, primary treatment, secondary treatment, tertiary treatment and ultimate disposal. It is suggested to the hotel to supervise the operation of WWTP so that the performance of WWTP is more optimal in reducing the pollution material produced.